Aeolian abrasion of the coastal deposits on the western Crete - Dulias, Renata (Quaestiones Geographicae, 2023)
Crete is located in the collision zone of tectonic plates; therefore, the island coast was often shaped due to tectonic phenomena. In 365 AD, a major earthquake caused the uplift of the coast of western Crete by a few metres. It means that the modern beaches of this part of the island are fragments of the former seabed with its littoral deposits. Some of these deposits are affected by wind activity. The article aims to answer the question, did wind transport lasting more than 1600 years give the marine deposits the features of aeolian deposits? Grain size and mineral composition were determined for samples from seven research sites in western Crete. Deposits representing three sedimentary environments were examined – high-energy beach, aeolian, and beach with permanent or periodic fluvial supply. Quartz abrasion was established using the morphoscopic method. In the 0.8–1.0 mm fraction, less resistant carbonate minerals dominate (on average, 77%), while the content of more resistant quartz is low (on average, 18%). It means most deposits are relatively young and were briefly in the range of aeolian processes. Coastal deposits are dominated by moderately rounded and mat grains EM/RM, on average 79%. The content of very well-rounded and mat grains RM is low, on average 18%. Multiple predominances of EM/RM grains in relation to RM grains indicate short-term aeolian transport. It can be concluded that the degree of aeolisation of coastal deposits by wind activity from 365 AD to the present is weak, at most moderate.